Crucial Roles of Abscisic Acid Biogenesis in Virulence of Rice Blast Fungus Magnaporthe oryzae - Spence, Carla A.; Lakshmanan, Venkatachalam; Donofrio, Nicole; Bais, Harsh P. (Frontiers in Plant Science, 2015)
Rice suffers dramatic yield losses due to blast pathogen Magnaporthe oryzae. Pseudomonas chlororaphis EA105, a bacterium that was isolated from the rice rhizosphere, inhibits M. oryzae. It was shown previously that pre-treatment of rice with EA105 reduced the size of blast lesions through jasmonic acid (JA)- and ethylene (ETH)-mediated ISR. Abscisic acid (ABA) acts antagonistically toward salicylic acid (SA), JA, and ETH signaling, to impede plant defense responses. EA105 may be reducing the virulence of M. oryzae by preventing the pathogen from up-regulating the key ABA biosynthetic gene NCED3 in rice roots, as well as a β-glucosidase likely involved in activating conjugated inactive forms of ABA. However, changes in total ABA concentrations were not apparent, provoking the question of whether ABA concentration is an indicator of ABA signaling and response. In the rice-M. oryzae interaction, ABA plays a dual role in disease severity by increasing plant susceptibility and accelerating pathogenesis in the fungus itself. ABA is biosynthesized by M. oryzae. Further, exogenous ABA increased spore germination and appressoria formation, distinct from other plant growth regulators. EA105, which inhibits appressoria formation, counteracted the virulence-promoting effects of ABA on M. oryzae. The role of endogenous fungal ABA in blast disease was confirmed through the inability of a knockout mutant impaired in ABA biosynthesis to form lesions on rice. Therefore, it appears that EA105 is invoking multiple strategies in its protection of rice from blast including direct mechanisms as well as those mediated through plant signaling. ABA is a molecule that is likely implicated in both tactics.